PAX9 gene mutations and tooth agenesis: A review - Bonczek, O; Balcar, V J; Šerý, O (Clinical genetics, 2017)
Paired box 9 (PAX9) is one of the best-known transcription factors involved in the development of human dentition. Mutations in PAX9 gene could, therefore, seriously influence the number, position and morphology of the teeth in an affected individual. To date, over 50 mutations in the gene have been reported as associated with various types of dental agenesis (congenitally missing teeth) and other inherited dental defects or variations. The most common consequence of PAX9 gene mutation is the autosomal-dominant isolated (non-syndromic) oligodontia or hypodontia. In the present review, we are summarizing all known PAX9 mutations as well as their nature and precise loci in the DNA sequence of the gene. Where necessary, we have revised the loci of the mutations in line with the reference sequence of the PAX9 gene as it appears in the current DNA databases.
Keywords: Animals; Mutation; Exons; PAX9 Transcription Factor; PAX9; transkripční faktor PAX9; anodoncie; Humans; oligodontia; hypodontia; gene; polymorfismus genetický; Anodontia; mutation; Polymorphism, Genetic; zvířata; exony; mutace; lidé